Air Pollution Variation During COVID-19 Pandemic Using Satellite and On-site Measurement Data in Six Provinces in Iran - Maryam Zare Shahne; Amirhossein Noori; Mehdi Alizade Attar (Numerical Methods in Civil Engineering)
In the present study, the temporal variation of Sentinel-5P TROPOMI-derived air pollutants (NO2 and SO2,) and MODIS-derived AOD were examined by using satellite missions in six air pollution’ hotspots provinces, including Isfahan, Tabriz, Mashhad, Tehran, Ahvaz, and Guilan in Iran for contemporaneous time periods before (as a baseline period), and during the epidemic, including the first wave lockdown period of the COVID-19 outbreak, from the 22nd of February, 2019, to the 22nd of February, 2021. The results revealed that the mean ratio of NO2 and SO2 has not varied drastically in the considered provinces. These column concentration ratios for all months were within the range of +2%(Tehran) to -6% (Tabriz). In comparison, the ratio of variance is more considerable, especially for Guilan province, a tourist attraction province, even in travel restrictions and lockdowns in Iran. The AOD distribution map and its trend illustrated that Guilan, Khorasan-Razavi, and Tabriz had become more pollutants after the outbreak due to changes in tourist patterns and emission inventories. Base on wavelet transform, implemented on ground-measurment of PM2.5, the PM2.5 concentration increased in early 2021 from the value in baseline period, due to eased restriction and expansion of public COVID-19 vaccine in all considered provinces.